Piracy : from the high seas to the digital age - Lombardo, Jennifer (World history (Lucent Press), 2019)
Describes piracy around the world from ancient times to today, debunking popular myths and offering factual information. Also discusses digital piracy. Includes a timeline, photographs, primary sources, and further resources.